Building cross-cutting skills and landscapes knowledge for effective youth leadership - Global Landscapes Forum (2014)
Conferences and committees the world over are recognizing the importance of youth representation. However, youth participation is still largely limited, particularly in the international arena, to a ‘demand to be heard’. Youth involvement can also often be tokenistic – where young people are given a voice but no decisionmaking power. Extensive surveys and interviews were conducted following the GLF showing a significant uptake of practical skills amongst youth leaders and masterclass participants that helped to maximize their participation in the GLF. Interviews conducted with senior professionals involved in youth activities at the GLF suggests the activities helped to foster intergenerational learning. This report offers our experiences, lessons, and suggestions from youth activities at the Lima Global Landscapes Forum (GLF 2014) as a concrete example of how meaningful participation of youth in conferences can be realized. A three-year ‘youth engagement in conferences’ strategy is currently under development, with the aim to secure long-term funding support in 2015. As part of this, we are exploring the possibility of a 12-month ‘youth in landscapes’ fellowship and mentoring program under the auspices of GLF.